Predictors of depression among caregivers of patients with severe mental illness in Northwest Ethiopia, 2023: an explanatory sequential mixed-method study - Munie, Birhanu Mengist; Birhan, Zelalem; Legas, Getasew; Asnakew, Sintayehu; Belete, Amsalu; Beyene, Getnet Mihretie; Shiferaw, Kirubel; Mulu, Anemut Tilahun; Kassie, Yohannes Tesfahun; Aytenew, Tigabu Munye; Tedla, Assasahegn (Frontiers in Psychiatry, 2024)
Severe mental illness results in an enormous social and economic burden on affected individuals, their families, and communities, especially in developing countries, such as Ethiopia.Objective: To assess the level of depression among caregivers of patients with severe mental illness in Debre Tabor Town, North West, Ethiopia in 2023.Methods: This institution-based explanatory mixed study was conducted at Debre Tabor Compressive Specialized Hospitals between September 30 and October 30, 2023. A systematic random sampling technique was used to select 260 study participants, and a public health questionnaire was used to assess depression.Epicollect5 was used to collect data, which were then exported to the SPSS-25 for analysis. Variables with a P-value <0.25 were considered candidates for the multivariate logistic regression analysis. The odds ratios with a 95% confidence interval were used to determine the strength of the association. An in-depth interview was conducted with 11 participants, selected using purposive sampling.The Prevalence of depression was 31.3% (95%, CI, 29.7, 38.6). The mMultivariate analysis showed that being female (AOD = 2.43, CI, 1.42-7.23), divorced/widowed (AOD = 1.8, CI = 1.32-6.34), poor social support (AOD = 2.2, CI = 1.9-5.87), and perceived stigma (AOD = 2.33, CI = 0.24-13.22) were negatively positively associated with depression. The qualitative results suggest that being female, illiterate, illness severity of the illness, lack of poor social support, and stigma were factors for depression.The prevalence of depression was high among caregivers of patients with severe mental illness. Female gender, being divorced or widowed, being illiterate, poor social support, and perceived stigma were the factors. This implies that a greater focus on caregivers and the government increases mental health literacy and mental health community services.